2021
DOI: 10.1007/s13762-021-03506-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mineral composition of ashes from wood biomass combustion in domestic wood-fired furnaces

Abstract: The paper presents the results of studies on ashes produced from burning wood biomass in closed wood-fired furnaces, in individual household furnaces (Silesian Province, Poland). Dry sieve analysis and detailed granulometric analysis were performed with the Analysette 22 Micro Tec plus analyser. Content of the basic elements (Al, Si, P, Na, K, Mg, Ca, Fe) and potentially toxic elements (As, Pb, Cd, Zn, Cu, Ni, Cr, Hg) was determined by atomic absorption spectrometry (AAS) and inductively coupled plasma mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…This is not desirable in solid biofuels. Birch wood and briquette were found to have ash contents of 18.3% and 10.7% respectively [ 39 ]. These ash content values were known to have great effect on the calorific value of the samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not desirable in solid biofuels. Birch wood and briquette were found to have ash contents of 18.3% and 10.7% respectively [ 39 ]. These ash content values were known to have great effect on the calorific value of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, high volatile matter is unwanted for solid biofuels and great efforts are made to reduce its content in the biofuel before utilization. Smołka-Danielowska et al [ 39 ] found that wood biomass is characterized by volatile matter content ranging between 69.3–81%. In a study on the production of solid biofuel from palm wastes, Yuliansyah et al [ 43 ] found that palm fronds and trunks had very high volatile matter of 82.5% and 83.9% respectively, which were not good for solid biofuels.…”
Section: Resultsmentioning
confidence: 99%
“…increase of fly ash content in mixtures, the concentration of heavy metals increases, which is in accordance with numerous authors' findings. 5,14,15 As, Ba, Cd and Pb appear in exchangeable fractions of both tested ash mixtures, which indicates direct leaching after disposal, and the higher the leaching the smaller ash particles are. 16 Pb was released the most from the Pd1 sample, in a concentration of 33.3 %, while 35.2 % of Pb was leached from the Pd2 sample.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…Lower average concentrations of Pb, Cd, Hg and As are emitted by spruce combustion, compared to the combustion of wood briquettes from deciduous trees. 15 Due to the increased emission of these elements, there is a risk that occurs during combustion in open fireplaces in households.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many studies on the elemental composition of wood ashes demonstrated wide variability in their contents due to different plant species, parts, and combustion temperatures (Huang et al, 1992; Semelová et al, 2008; Smołka‐Danielowska & Jabłońska, 2022). The contents of soil nutrients, for example, P, Ca, K, Cu, and Zn, are often reported in different wood ashes, providing a basis for the recent use of wood ashes in some agricultural fields (Semelová et al, 2008; Wierzbowska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%